Access to water and payment for environmental services, Jequetepeque Watershed, Peru - Kim Raben (Danish Institute for International Studies (DIIS), 2007)
The project “Payment for environmental services as a mechanism for promoting rural development in the upper watersheds of the tropics” is a research and development project running in four pilot catchments in the Andes region. Its overall objective is to alleviate poverty and enhance sustainability in upper catchments by increasing the flow of resources from governments and civil society to poor rural producers, reducing the negative impact of environmental externalities and strengthening the competitive capacity of the poor. DIIS has been given the task to carry out an institutional analysis in order to identify key stakeholders in the management of watersheds, their priorities and interests, their mutual relations and issues contributing to conflict and cooperation among them. The present Working Paper presents the findings from the institutional analysis carried out in Jequetepeque watershed, Peru. The paper argues that the introduction of PES schemes takes place in a context of already existing institutions and competition over access to land and water. Moreover, the introduction of PES schemes itself represents the creation of new forms of rules and regulations (or PES institutions), which might shape existing property institutions. The design of PES schemes has to be considered with a view to how it might influence the existing institutions governing access to irrigation water and the actual distribution of access to irrigation water and vice versa. The national water legislation for irrigation constitutes the framework which shapes access and management of water for irrigation and thereby also influences the circumstances under which PES schemes can be implemented. Two types of water titles can be established. Either water users can possess a licencia, which gives a permanent and secure right to water, or a permiso, which only gives rights to water if total available quantities exceed the needs of the holders of permanent water rights (licencia) Based on an analysis of rural inhabitants' access to irrigation water, the paper concludes by listing the challenges associated with the wish to establish pro-poor PES in the watershed: The administration and enforcement of the formal regulations on water rights and use is weak and in several cases non-existing. In many villages, water users do not pay fees for the water they are allocated, or they withdraw water to which they are not entitled according to existing water rights. The illegal use of water and lack of payment of fees for legally endorsed water use indicate great risks for implementing a PES system based on individual payments. A better understanding of who enjoys illegal access to water – i.e. the poor or the non-poor; farmers with secure water rights (licencia), with insecure water rights (permiso), or without any water rights – is fundamental to assess the poverty impact of strengthening water rights administration in general and introducing PES schemes in particular. Secure rights are a pre-condition for the PES market on the supply and the demand site. On the supply side, it should be considered to which extent the current land tenure rights, of which many remain without legal documents, will affect negatively the possibility of establishing schemes. On the supply side, it should be considered how a more secure delivery of water to water right holders will improve the security of their rights. Unclear tenure rights constrain the establishment of contracts. The current system where some hold licencias and others permisos might cause some water right holders to be willing to participate while others do not wish to be involved. As all water users benefit from the same source a free-rider problem might occur. Propoor impacts of a PES scheme are questionable in the case of Jequetepeque watershed as the poorest cannot be targeted as providers or beneficiaries of water services. It should be expected that streams of benefits (cash to providers and improved environmental services) are likely to create incentives for elites to take over land or strengthen their water rights. Thus safeguards need to be included to guard against elite capture.
Keywords: 330; Wasserversorgung; Wasserpreis; Umweltkosten; Peru